Henry's daughters (National Institute for Engineering Ethics, [Texas Tech University], 2010)
Henry's daughters is designed to raise awareness of the ethical aspects of engineering work, advance knowledge and understanding of professional standards and public obligations and expectations, improve skills in moral reasoning, and strengthen personal dedication to exemplary conduct.